In vitro efficacy of Metarhizium anisopliae sensu lato against unfed Amblyomma parvum (Acari: Ixodidae) - Garcia, Marcos Valerio (2018)
Amblyomma parvum Aragão (Acari: Ixodidae) is a tick species found with wide distribution in the Neotropical region. Even though it is a wildlife-related tick, it is also a frequent parasite of domestic animals, is aggressive to human beings and may harbor pathogenic microorganisms. Therefore, it is a target species for control on domestic animals, particularly those at the rural–wildlife interface. Herein, the efficacy of two isolates (E9 and IBCB 425) of an entomopathogenic fungus, Metarhizium anisopliae sensu lato, already evaluated for ticks that parasitize domestic animals, was tested against unfed A. parvum adults. Both isolates displayed high acaricidal efficacy after immersion in fungal conidial suspensions for 5 min. Isolate E9 killed all ticks by the 7th day post-treatment, and isolate IBCB 425 did so by the 11th day. Tick mortality of 80 and 90% was achieved as early as the 3rd and 4th days, respectively, with both treatments. Thus, if a commercial M. anisopliae s.l. acaricide against domestic animal ticks is developed, it would also be effective against A. parvum.